2012
DOI: 10.1007/s12105-012-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus-16 Associated Adenocarcinoma NOS of Base of Tongue

Abstract: The causative role of human papillomavirus (HPV) in a subset of squamous cell carcinomas of the oropharynx (OSCC) is now well established with HPV-16 being detected in approximately 92 % of HPV-positive OSCC in North America. Recently HPV has also been found in some non-squamous oropharyngeal carcinomas including adenosquamous carcinomas, neuroendocrine carcinomas, and undifferentiated ''lymphoepithelioma-like'' carcinomas. Herein, we report a HPV-16 positive adenocarcinoma NOS arising in the base of the tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It is our hope and expectation that the description of this entity herein will lead to recognition of similar cases by others. Indeed, while this study was in preparation, Perez-Ordoñez and colleagues [12] reported a single patient with an HPV-associated adenocarcinoma of the base of the tongue, with comparable histologic and immunophenotypic features, although long-term follow-up was not available. We would propose that for adenocarcinomas arising in the oropharynx, or for metastatic adenocarcinomas of unknown primary in neck lymph nodes showing a prominent cystic component, the consideration of an HPV association may be particularly appropriate.…”
Section: Discussionmentioning
confidence: 98%
“…It is our hope and expectation that the description of this entity herein will lead to recognition of similar cases by others. Indeed, while this study was in preparation, Perez-Ordoñez and colleagues [12] reported a single patient with an HPV-associated adenocarcinoma of the base of the tongue, with comparable histologic and immunophenotypic features, although long-term follow-up was not available. We would propose that for adenocarcinomas arising in the oropharynx, or for metastatic adenocarcinomas of unknown primary in neck lymph nodes showing a prominent cystic component, the consideration of an HPV association may be particularly appropriate.…”
Section: Discussionmentioning
confidence: 98%
“…We present an additional case of HPV-associated adenocarcinoma, NOS, of the BOT, along with the updated clinical history and molecular testing of the three previously reported cases [9,10]. As in prior reports, this adenocarcinoma showed no morphologic or immunophenotypic features of a named salivary type carcinoma.…”
Section: Discussionmentioning
confidence: 53%
“…HPV-associated oropharyngeal SCC treated from 1983 to 2013 at the University of Pittsburgh Medical Center and identified as part of a prior project (n = 89) [20] were re-reviewed with the knowledge of HPV-associated adenocarcinoma, NOS, of the BOT [9,10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations